2022
DOI: 10.3389/fimmu.2022.1020927
|View full text |Cite
|
Sign up to set email alerts
|

Expanding spectrum, intrafamilial diversity, and therapeutic challenges from 15 patients with heterozygous CARD11-associated diseases: A single center experience

Abstract: CARD11-associated diseases are monogenic inborn errors of immunity involving immunodeficiency, predisposition to malignancy and immune dysregulation such as lymphoproliferation, inflammation, atopic and autoimmune manifestations. Defects in CARD11 can present as mutations that confer a complete or a partial loss of function (LOF) or contrarily, a gain of function (GOF) of the affected gene product. We report clinical characteristics, immunophenotypes and genotypes of 15 patients from our center presenting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Clinically, patients with CADINS usually present early onset atopy (AD, asthma, food allergies, and eosinophilic esophagitis), recurrent viral skin and respiratory tract infections ( 35 ). In a recent single center cohort study, AD and skin infections ameliorated or even resolved during adolescence, suggesting a spontaneous dermatological improvement over time ( 36 ).…”
Section: Pathogenetic Mechanism and Treatment Of Ieis-a With Skin Inv...mentioning
confidence: 99%
“…Clinically, patients with CADINS usually present early onset atopy (AD, asthma, food allergies, and eosinophilic esophagitis), recurrent viral skin and respiratory tract infections ( 35 ). In a recent single center cohort study, AD and skin infections ameliorated or even resolved during adolescence, suggesting a spontaneous dermatological improvement over time ( 36 ).…”
Section: Pathogenetic Mechanism and Treatment Of Ieis-a With Skin Inv...mentioning
confidence: 99%
“…The clinical symptoms of this patient were mild and did not practice a formal HLH treatment, but dexamethasone was taken orally for maintenance therapy 7 . Recently, Luciano Urdinez reported a 2‐year‐old BENTA patient with CARD11 G123S mutation 8 . The patient developed recurrent and refractory HLH fulfilling six criteria, including fever, cytopenias, hepatosplenomegaly, hypertriglyceridaemia, hyperferritinaemia, hypofibrinogenaemia and elevated soluble CD25 8 .…”
Section: Introductionmentioning
confidence: 97%
“…8 This patient suffered HLH with a severe clinical course and a fatal outcome in early childhood. 8 The overlapping clinical manifestations of BENTA disease and HLH often pose diagnostic dilemmas and delay in definitive therapy, leading to adverse clinical consequences. In this study, we reported a 15-month-old boy diagnosed as BENTA meeting with diagnostic criteria of HLH, expanding the clinical manifestations and immunological features of BENTA disease.…”
mentioning
confidence: 97%
See 2 more Smart Citations